UPAYA MENINGKATKAN KEMAMPUAN LITERASI SISWA MELALUI PEMBUATAN POJOK BACA PADA PERPUSTAKAAN DI UPTD SDI MENGERUDA - Jenia, Maria; Meka, Marsianus; Efrida Ita; Ngura, Elisabeth Tantiana (Global Action and Education for Society, 2025)
The reading corner is an effective facility located in the corner of the room in the library which is useful for providing access to all school members to read books. Creating a reading corner can also improve student literacy. So this research aims to increase student literacy at the UPTD SDI Mengeruda elementary school which is carried out through the creation of a reading corner. This type of research uses qualitative methods. Data collection techniques use observation, interviews and documentation methods. The subjects of this research were all school residents at UPTD SDI Mengeruda with a total of 139 students. Based on the results of observations made by researchers, the creation of a reading corner has not been implemented at the school. So this research is able to create new ideas for increasing student literacy by creating a reading corner in the library at UPTD SDI Mengeruda. The results of the research can be concluded that with a reading corner, students can use the reading corner as a comfortable and attractive place to increase students' interest in reading. There has been an increase in interest in reading in 95% of 139 children.